Dressing SMART For Girls - Jill Lowe
Dressing Smart for Girls provides smart, practical and cost-effective dressing strategies for teenage girls grappling with dressing issues in an image-conscious society. Designed for young teenage girls, the book comes in a visually-appealing and colourful format that is underpinned by a magazine- style design.